PENGARUH STRES, KEPUASAN KERJA DAN SELF-LEADERSHIP TERHADAP KINERJA PEGAWAI PT. BPR KHRISNA DARMA ADIPALA (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
Human resources continue to be the central focus and backbone for companies to maintain their operations. The vital role of human resources is apparent in all company activities. The study was carried out at PT BPR Khrisna Darma Adipala in Badung Regency, with a sample of 50 employees serving as respondents, employing a saturated sampling method for sampling. Data collection involved the use of questionnaires, interviews, observations, and documentation. Data analysis involved the application of multiple linear regression analysis with SPSS version 25. The findings indicate that work-related stress detrimentally affects employee performance, suggesting that heightened stress levels correspond to diminished performance at PT BPR Khrisna Darma Adipala in Badung Regency. Conversely, job satisfaction positively influences employee performance, indicating that higher satisfaction levels correspond to better performance at PT BPR Khrisna Darma Adipala in Badung Regency. Moreover, self-leadership also yields a positive impact on employee performance, indicating that an increase in self-leadership is associated with improved performance at PT BPR Khrisna Darma Adipala in Badung Regency.
Keywords: employee performance; job satisfaction; job stress; self leadership